Twenty Three Years: The Acceptance of Maxwell’s Equations - Rautio, James C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Maxwell first published what came to be called “Maxwell’s equations” in 1865. However, it was not until 1888, and Heinrich Hertz’s experimental validation, that Maxwell’s equations were widely accepted as correct. The story of the intervening 23 years is little known. Maxwell, who died in 1879, was exceptionally modest and did not promote his own results at any time. The survival of Maxwell’s equations was up to the only three researchers in the entire world who paid serious attention to Maxwell’s paper in 1865, and his seminal Treatise in 1873: Oliver Heaviside, Oliver Lodge, and George Francis FitzGerald. Later, Hertz joined the group forming “The Four Maxwellians”. In this paper, we describe the torturous 23 year path Maxwell’s equations took from their creation to their initial acceptance.